STATISTICAL METHOD FOR A HYDRAULIC CONDUCTIVITY ESTIMATE USING EMPIRICAL FORMULAS - Dulovičová, Renáta; Ovcharovichova, Janka; Velísková, Yvetta (Journal of Applied Engineering Science, 2022)
Sediment’s hydraulic conductivity is one of the key inputs for estimating solute and water movement in a vadose zone. Laboratory and field measurements are time consuming and subject to substantial inaccuracies. Thus numerous empirical formulas have been adopted to predict hydraulic conductivity from measurable soil properties such as grain size distribution, soil temperature or bulk density. The objective of this study was twofold: (1) assess the hydraulic conductivities calculated from empirical formulas and (2) develop a simple method to estimate hydraulic conductivities for clayey sand sediments. Using sediment samples extracted from irrigation canals in Zitny Ostrov, Southern Slovakia, we evaluated fourteen empirical formulas. Three sets of parameters were assessed using common statistical methods. The sets included computed hydraulic conductivities, logarithmically transformed hydraulic conductivities, and measured values of hydraulic conductivities. Field measurements and laboratory investigations of hydraulic conductivities were performed to supplement our empirical calculations. The three sets of parameters were compared and formed the foundation for developing an original regression equation: Ksat me = 0.019 (LTKsat)2 + 0.183 (LTKsat) + 4.863– an equation that captures the variables with reasonable agreement. The logarithmically transformed and measured values correlated, yielding R2 = 0.945. Thus, the measured values validated our regression equation.